Enzymatic Electroanalytical Biosensor Based on Maramiellus colocasiae Fungus for Detection of Phytomarkers in Infusions and Green Tea Kombucha - Érica A. Batista; Giovanna N. M. Silva; Livia F. Sgobbi; Fabio B. Machado; Isaac Y. Macedo; Emily K. Moreno; Jerônimo R. Neto; Paulo S. Scalize; Eric S. Gil (Biosensors, 2021)
In this work, we developed an enzymatic voltammetric biosensor for the determination of catechin and gallic acid in green tea and kombucha samples. The differential pulse voltammetry (DPV) methodology was optimized regarding the amount of crude enzyme extract, incubation time in the presence of the substrates, optimal pH, reuse of the biosensor, and storage time. Samples of green tea and kombucha were purchased in local markets in the city of Goiânia-GO, Brazil. High performance liquid chromatography (HPLC) and Folin-Ciocalteu spectrophotometric techniques were performed for the comparison of the analytical methods employed. In addition, two calibration curves were made, one for catechin with a linear range from 1 to 60 µM (I = −0.152 * (catechin) − 1.846), with a detection limit of 0.12 µM and a quantification limit of 0.38 µM and one for gallic acid with a linear range from 3 to 60 µM (I = −0.0415 * (gallic acid) − 0.0572), with a detection limit of 0.14 µM and a quantification limit of 0.42 µM. The proposed biosensor was efficient in the determination of phenolic compounds in green tea.